PERAN E-COMMERCE DALAM TRANSFORMASI DIGITAL UMKM BERBASIS SYARIAH UNTUK MENINGKATKAN DAYA SAING PASAR - Azyumardi Azra Madani; Muhammad Riki Saputra; Mega Silvia; Nurul Fajriani; Yuliyanti Yuliyanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The advancement of digital technology has brought significant changes to Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, including Sharia-based MSMEs. This digital transformation is crucial to enhancing market competitiveness, expanding market access, and improving operational efficiency. One of the key instruments in the digital transformation of MSMEs is e-commerce. This study aims to analyze the impact of e-commerce in driving the digital transformation of Sharia-based MSMEs and its effect on market competitiveness, with a focus on the Tegal Gubug Market in Cirebon Regency. The study uses a quantitative approach with a descriptive-quantitative method, relying on secondary data. The findings show that the integration of digital technology and Sharia principles in e-commerce can enhance the competitiveness of MSMEs, although challenges in technology adoption remain an obstacle. These findings provide insights for Sharia-based MSME entrepreneurs to formulate digital strategies in accordance with Islamic values, while improving their business performance in the face of digital market competition.